Functional benefits of Tai Chi training within senior housing facilities - Manor, Brad (2014)
OBJECTIVES: To determine the effects of Tai Chi training on functional performance and walking with and without performance of a cognitive task, in adults of advanced age living within supportive housing facilities. DESIGN: Secondary data analysis of a single-blind, randomized controlled trial of Tai Chi training versus an attention-matched educational control intervention with cross-over to Tai Chi. SETTING: Two supportive housing facilities. PARTICIPANTS: Sixty-six men and women living in supportive housing facilities entered the study. Fifty-seven participants aged 87±7 years completed all study procedures. INTERVENTION: Interventions consisted of two, one-hour, instructor-led group sessions/week for 12 weeks. Tai Chi training consisted of movements based upon the Yang-style short form. Educational sessions consisted of lectures and discussions of age-related health topics. MEASUREMENTS: Subjects were tested for physical function (Short Physical Performance Battery, SPPB), balance (Berg Balance Scale, BBS), mobility (timed up-and-go, TUG), and walking speed under normal and cognitive dual task conditions. RESULTS: The Tai Chi group exhibited greater (p=0.005) improvement in SPPB scores (baseline=8.1±2.9, follow-up=9.0±2.6) compared to controls (baseline=8.2±2.6, follow-up=8.2±2.6). Tai Chi also increased normal and dual task walking speeds (p<0.001), yet did not affect BBS (p=0.02) or TUG (p=0.02) after accounting for multiple comparisons. The dual task cost (i.e., percent change) to walking speed was unaffected. Following the cross-over Tai Chi intervention, the control group improved performance in the SPPB, BBS, and TUG, and increased walking speed under normal and dual task conditions (p<0.008). CONCLUSION: Tai Chi training may be a safe and effective therapy to help improve physical function and dual task walking in very old adults living within supportive housing facilities.